Does sealing endotracheal tube cuff pressure diminish the frequency of postoperative laryngotracheal complaints after nitrous oxide anesthesia? - Braz, José Reinaldo Cerqueira [UNESP]; Volney, A.; Navarro, LHC; Braz, Leandro Gobbo [UNESP]; Nakamura, G. (Elsevier B.V., 2004)
Study Objectives: To study endotracheal tube (ETT) cuff pressures during nitrous oxide (N2O) anesthesia when the cuffs are inflated with air to achieve sealing pressure, and to evaluate the frequency of postoperative laryngotracheal complaints.Design: Prospective, randomized, blind study.Setting: Metropolitan teaching hospital.Patients: 50 ASA physical status I and II patients scheduled for elective abdominal surgery.Interventions: Patients received standard general anesthesia with 66% N2O in oxygen. In 25 patients, the ETT cuff was inflated with air to achieve a sealing pressure (P-seal group). In 25 patients, the ETT cuff was inflated with air to achieve a pressure of 25 cm H2O (P-25 group).Measurements and Main Results: ETT intracuff pressures were recorded before (control) and at 30, 60, 90, 120, and 150 minutes during N2O administration. We investigated the frequency and intensity of sore throat, hoarseness, and dysphagia in patients in the Post-Anesthesia Care Unit (PACU) and 24 hours following tracheal extubation. The cuff pressures in the P-seal group were significantly lower than in the P-25 group at all time points studied (p < 0.001), with a significant increase with time in both groups (p < 0.001). The cuff pressures exceeded the critical pressure of 30 cm H2O only after 90 minutes in the P-seal group and already by 30 minutes in the P-25 group. The frequency and intensity of sore throat, hoarseness, and dysphagia were similar in both groups in the PACU and 24 hours after tracheal extubation (p > 0.05).Conclusions: Minimum ETT sealing cuff pressure during N2O anesthesia did not prevent, but instead attenuated, the increase in cuff pressure and did not decrease postoperative laryngotracheal complaints. (C) 2004 by Elsevier B.V.
Keywords: anesthetic gases : nitrous oxide; dysphagia; equipment and supplies : endotracheal tube cuff; intubation : intratracheal; sore throat